IS6110 restriction fragment length polymorphism typing of Mycobacterium tuberculosis isolates from East Azerbaijan Province of Iran - Mohamad Asgharzadeh; Karen Shahbabian; Jafar Majidi; Ahmad Mirza Aghazadeh; Cirus Amini; Ali Reza Jahantabi; Abdolnaser Rafi (Memorias do Instituto Oswaldo Cruz, 2006)
To investigate the genetic variation among Mycobacterium tuberculosis isolates in the East Azerbaijan Province of Iran and to evaluate the level of and risk factors for recent transmission of tuberculosis (TB), we performed IS6110-based restriction fragment length polymorphism analysis of strains, isolated from 105 patients during the period of September 2002 to March 2003 in TB centers and university hospitals of the province. Among 105 isolates, 81 different IS6110 patterns were found, of which 70 were observed only once and 11 were shared by two to eight isolates. Ninety-six isolates (91.4%) were found to have more than five copies of IS6110 and together with high patterns polymorphism, shows that IS6110-RFLP typing could be useful for studying the epidemiology of TB in Azerbaijan. The minimum estimated rate of recent transmission was 23%, suggesting that the degree of recent transmission in East Azerbaijan Province is relatively low. Clustering was not associated with age, sex or site of infection of TB but drug-resistant isolates were less likely to be clustered than sensitive isolates (p < 0.05).